Clinical benefit of direct oral anticoagulants vs. vitamin-K antagonist in octogenarians with atrial fibrillation. (14th October 2021) - Bonanad, C; Garcia-Blas, S; Diez Villanueva, P; Ariza, A; Tarazona, F J; Bertomeu-Gonzalez, V; Facila, L; Torres, J; Nunez, J; Cordero, A
Abstract: Background: Direct oral anticoagulants (DOACs) have demonstrated to the be more effective and safer than vitamin-K antagonist (VKA) for stroke prevention in patients with atrial fibrillation (AF). AF prevalence increases exponentially with age but octogenarians were underrepresented in clinical trials. Methods: We performed a metanalysis with currently available studies that assessed the effect of DOACS vs. VKA in patients with age ≥80 and AF after performing a systematic search. The primary endpoints analyzed were stroke and all-cause death. Secondary endpoints were major bleeding, according to each study definitions, intracranial bleeding and gastrointestinal (GI) bleeding. The raw numbers of incident end-points reported in each study were used. A random effects model was selected because significant heterogeneity was observed; sensitivity analyses tested potential sources of heterogeneity, publication bias and the small-study effect. Results: A total of 147, 067 patients from 16 studies were included, 71, 913 treated with DOACs and 75, 154 with VKA. Inclusion criteria for the study was age ≥80 in 13 studies, ≥85 in two and ≥90 in one. Mean age of patients included all the studies was 86.2 (2.6) years. According to the study drug, 34, 448 received rivaroxaban; 20, 295 apixaban; 14, 641 dabigatran, 492 edoxaban and; 2, 037 any DOAC. No difference in mean age was observed according to the study drug. Stroke incidence was available in the 16 studies. DOACs treatment was associated to 28% reduction of stroke (RR: 0.72 95% CI 0.63–0.82; p<0.001) (figure). All-cause mortality could be assessed in 12 studies and DOACs treatment was associated to 18% in mortality (RR: 0.82, 95% CI 0.70–0.96; p=0.012) (figure). DOACs treatment was not associated to reductions in major bleeding (RR: 0.85, 95% CI 0.69–1.04; p=0.108); in contrast, the highest effect of DOACs treatment was a 43% reduction of intracranial bleeding (RR: 0.47, 95% CI 0.36–0.60; p<0.001) (Figure 4). Finally, DOACs treatment was not associated higher of GI bleeding risk (RR: 1.08, 95% CI 0.76–1.53; p=0.678). Metaregression identified inclusion site in North-America (p<0.001), the ELDERCARE-AF results (p=0.023), control arm different than VKA (p=0.006) and the prevalence of hypertension (p=0.042) were outlined as main sources of heterogeneicity for stroke risk reduction. The type of DOAC was the main source of source of heterogeneicity for all-cause mortality (p<0.001) and major bleeding (p=0.03) risk reduction. No small-study effect was found for any endpoint except for intracranial bleeding (Harbor test p=0.029). Conclusions: Treatment with DOACs in octogenarians reduces the incidence of stroke, all-cause mortality and intracranial bleeding as compared to VKA. FUNDunding Acknowledgement: Type of funding sources: None.